A Characterization of Women Living with HIV in Belgium - Rakan Nasreddine; Jean Cyr Yombi; Gilles Darcis; Maartje Van Frankenhuijsen; Lida Van Petersen; Chloé Abels; Sofia Dos Santos Mendes; Marc Delforge; Stéphane De Wit (AIDS Research and Treatment)
Objectives. The primary objective of this study was to characterize women living with HIV (WLWH) in Belgium. The secondary objective was an exploratory analysis comparing women and men living with HIV (MLWH). Methods. This was a cross-sectional, observational, multicenter study. Inclusion criteria for the primary objective were all adult treatment-naïve and experienced WLWH actively being treated at one of the participating centers. For the secondary objective, inclusion criteria were all adult naïve and experienced women and MLWH, actively being treated at a single participating center. Data were collected between December 2022 and March 2023. A multivariable analysis was performed on all women included to evaluate for associations with having hypertension (HTN) or being virologically nonsuppressed (HIV-1 VL ≥200 copies/mL). In the exploratory analysis of women and MLWH, a multivariable analysis was carried out to evaluate whether female gender was associated with having HTN or being virologically nonsuppressed. Results. Overall, 2797 WLWH were included. The majority were Black (73.5%) and 48.5% were aged ≥50 years. The most common comorbidity was HTN (17.3%) and most individuals were virologically suppressed (HIV-1 VL <50 copies/mL; 85.6%). Black race was associated with having HTN (p<0.0001). Prior AIDS-defining illness (p=0.02) and a CD4+ T-cell count <500 cells/µL (p<0.0001) were associated with being nonsuppressed. A total of 1094 WLWH and 1878 MLWH were included in the exploratory analysis. HTN was higher among WLWH (20.2% vs. 12% MLWH). Female gender was not found to be associated with having HTN (p=0.86) or being nonsuppressed (p=0.14). Conclusion. In this analysis of WLWH in Belgium, the results depict an ageing population that is predominantly Black. The most common comorbidity observed was HTN. Women had a low rate of virologic nonsuppression, and female gender was not associated with being nonsuppressed.